1997
DOI: 10.1002/(sici)1097-0010(199706)74:2<257::aid-jsfa801>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Physical Indices, Processing Yields, Compositional Parameters and Fatty Acid Profile of Three Species of Cultured Sturgeon (Genus Acipenser)

Abstract: : Cultured Siberian sturgeon (Acipenser baeri), Adriatic sturgeon (Acipenser naccarii) and white sturgeon (Acipenser transmontanus) of market size were examined for condition factor, eviscerated and dressed yields, white Ñesh yield, viscera-, hepato-somatic-and gonado-somatic indices. Muscle pH, chemical composition, cholesterol content and fatty acid proÐle of Ñesh were also determined. SigniÐcant di †erences were noted between species in eviscerated yield and white Ñesh yield (lowest in A naccarii, highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The total content of the latter two acids in the parent forms ranged from 10.55 to 14.95%; in SSZ it amounted to 5.88%. This value lies within the value range found out by Badiani et al (1997) for the three sturgeon species bred in aquaculture. These acids are found in much higher amounts in bred fish than in those living in the wild, which was shown for Gulf sturgeon (Acipenser oxyrinchus desotoi), pikeperch (Stizostedion lucioperca) and turbot (Scophthalmus maximus) (Chen et al, 1995;Sérot et al, 1998;Jankowska et al, 2003).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The total content of the latter two acids in the parent forms ranged from 10.55 to 14.95%; in SSZ it amounted to 5.88%. This value lies within the value range found out by Badiani et al (1997) for the three sturgeon species bred in aquaculture. These acids are found in much higher amounts in bred fish than in those living in the wild, which was shown for Gulf sturgeon (Acipenser oxyrinchus desotoi), pikeperch (Stizostedion lucioperca) and turbot (Scophthalmus maximus) (Chen et al, 1995;Sérot et al, 1998;Jankowska et al, 2003).…”
Section: Resultssupporting
confidence: 85%
“…According to Badiani et al (1997), significant differences were observed between the water, fat and protein content in the tissue of the three sturgeon species; Acipenser baeri, A. naccari and A. transmontanus. Interestingly, the protein content ranged from 186.4 to 194.7 g/kg, but the fat content range was broader -from 44.9 to 106.4 g/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Fish lipids contain high level of PUFA and are a good source of PUFA for the human diet (Ackman and others 1972; Ackman 1999). The fatty acid profiles of sturgeon muscle tissue were dominant of MUFAs than saturated fatty acids and PUFAs (Badiani and others 1997). The contents of ω‐3 fatty acids of sturgeon meat were different between species of sturgeon (Badiani and others 1997) and wild or cultured sturgeon (Chen and others 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid profiles of sturgeon muscle tissue were dominant of MUFAs than saturated fatty acids and PUFAs (Badiani and others 1997). The contents of ω‐3 fatty acids of sturgeon meat were different between species of sturgeon (Badiani and others 1997) and wild or cultured sturgeon (Chen and others 1995). Xu and others (1993) reported increased level of EPA and DHA in white sturgeon tissue by the addition of cod liver oil in the fish diet.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to sturgeon flesh, the majority of researches found a relation between diet and caviar composition (Badiani et al . ; Zhang et al . ).…”
Section: Caviar and Aquaculture: The Bright Side Of The Moonmentioning
confidence: 99%